Physics of Nanostructured Solid State Devices - Bandyopadhyay, Supriyo (New York : Springer, 2012)
Physics of Nanostructured Solid State Devices introduces readers to theories and concepts such as semi-classical and quantum mechanical descriptions of electron transport, methods for calculations of band structures in solids with applications in calculation of optical constants, and other advanced concepts. The information presented here will equip readers with the necessary tools to carry out cutting edge research in modern solid state nanodevices.
Includes bibliographical references.; Index 547-551p.
Keywords: Nanostructured device; Solid state devices; Physics